2007
DOI: 10.1016/j.eplepsyres.2007.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Young patients with focal seizures may have the primary motor area for the hand in the postcentral gyrus

Abstract: SummaryObjective: We determined whether the primary motor hand area was most frequently located in the precentral gyrus in young patients with intractable focal seizures. Methods:Sixty-five patients with focal seizures aged between 5 months and 20 years who underwent a two-stage epilepsy surgery using chronic subdural-EEG monitoring were studied. Pairs of subdural electrodes were electrically stimulated, and the brain region with contralateral hand movement induced by the lowest-intense stimulus was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 40 publications
5
49
0
Order By: Relevance
“…More generally, recent data have also suggested that the functional segregation between M1 and S1 might not be as strict as initially postulated by Penfield [53]. In humans, in particular, it was found that the hand 'hot spot', defined as the cortical area that evokes hand or finger responses at the lowest electrical intensity, was located in the post-central gyrus in a significant fraction of subjects [54,55]. At a first level, this puzzling result highlights the necessity of considering Penfield's anatomical maps with caution.…”
Section: Mapping the Sensorimotor Systemmentioning
confidence: 92%
“…More generally, recent data have also suggested that the functional segregation between M1 and S1 might not be as strict as initially postulated by Penfield [53]. In humans, in particular, it was found that the hand 'hot spot', defined as the cortical area that evokes hand or finger responses at the lowest electrical intensity, was located in the post-central gyrus in a significant fraction of subjects [54,55]. At a first level, this puzzling result highlights the necessity of considering Penfield's anatomical maps with caution.…”
Section: Mapping the Sensorimotor Systemmentioning
confidence: 92%
“…ESM, using the method previously established [Fukuda et al, 2008; Haseeb et al, 2007], was performed as part of the clinical care during extraoperative electrocorticography recordings. A pair of subdural electrodes was stimulated by an electrical pulse-train of 5-s maximum duration using pulses of 300 μs duration and frequency of 50 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…However, ESM is not an ideal diagnostic modality, because of its insensitivity to find the motor areas in young children [Chitoku et al, 2001; Haseeb et al, 2007; Wylle and Awad, 1991]. A previous study reported that no contralateral hand movement was elicited by electrical stimulation in 15 of 65 children, and that the average age of these 15 patients was 3.4 years [Haseeb et al, 2007]. Inevitable limitations of ESM also include sampling errors; for example, the primary motor leg area is difficult to localize by ESM, unless subdural electrodes are placed exactly on the cortical tissues of interest in the interhemispheric fissure.…”
Section: Introductionmentioning
confidence: 99%
“…It is the third standardized moment, γ 1 and is defined as: (2) where 3 μ is the third moment about the mean and σ is the standard deviation. …”
Section: Feature Extractionmentioning
confidence: 99%
“…Newer methods where parts of the brain are electrically stimulated to avoid the onset of seizure are being developed [2]. Automatic detection of seizures forms an integral part of such methods.…”
Section: Introductionmentioning
confidence: 99%